Heterospilus Haliday, 1836 (Hymenoptera: Braconidae, Doryctinae) from China with a key to species - Tang, Pu; Belokobylskij, Sergey A.; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2013)
The Chinese species of the genus Heterospilus Haliday, 1836 from the Parasitic Hymenoptera Collection of Zhejiang Uni-versity were studied and thirty-four species are recognized, including 12 previously described species. Eighteen new spe-cies of this genus are described and illustrated: Heterospilus (Heterospilus) alternicoloratus sp. nov., H.(H.) balicyba sp. nov., H.(H.) chui sp. nov., H.(H.) curvisulcus sp. nov., H.(H.) densistriatus sp. nov., H.(H.) fujianensis sp. nov., H.(H.) jianfengensis sp. nov., H.(H.) liui sp. nov., H.(H.) longiventrius sp. nov., H.(H.) nanlingensis sp. nov., H.(H.) parvus sp. nov., H.(H.) prodigiosus sp. nov., H.(H.) punctatus sp. nov., H.(H.) qingliangensis sp. nov., H.(H.) semidepressus sp. nov., H.(H.) setosiscutum sp. nov., H.(H.) setosus sp. nov., and H.(H.) tenuitergum sp. nov. Seven species of Heterospilus are recorded for China for the first time: H. (Eoheterospilus) rubrocinctus (Ashmead, 1905), H.(H.) alboapicalis Beloko-bylskij, 1994, H.(H.) ater Fischer, 1960, H.(H.) cephi Rohwer, 1925, H.(H.) kerzhneri Belokobylskij et Maetô, 2009, H.(H.) tauricus Telenga, 1941, and H.(H.) tulyensis Belokobylskij, 1994. Two new synonyms are proposed: H. asiaticola Belokobylskij et Maetô, 2009 with H. chinensis Chen et Shi, 2004 and H. gracilis Shi et Chen with H. separatus Fischer, 1960. A key to the Chinese species of Heterospilus is provided.